Text Relationship with Power (Study of Critical Discourse Analysis of the Culture of Malay Parable in Tafsir Al-Azhar by Hamka) - Hakim, Lukman Nul (International Journal of Psychosocial Rehabilitation, 2020)
— The Malay Culture Parable is present as a text of Hamka’s Tafsir Al-Azhar, not only does it show the suitability of meaning with the text of the Qur’anic verse being interpreted by Hamka, but behind the text it shows it as a text of authority discourse. Through a discourse analysis approach with a critical paradigm offered by Norman Fairclough, there are three dimensions: first, the text of the power of discourse is related to Sukarno as the actor of power "an individual cult"; second, based on historical context, the text of the power of authority is related primarily to the "presidential decree" event of 5 July 1959, which changed the system of government from parliamentary democracy to guided democracy; and third, the relation of the authority text of the power of "individual cult" with social culture in Indonesia becomes strong because of the feudal culture that has not been uprooted from its roots.